The Role of Endoscopic Sinus Surgery in Children Undergoing External Drainage of Non-Medial Subperiosteal Orbital Abscess. Issue 3 (May 2021) - Chorney, Stephen R.; Buzi, Adva; Rizzi, Mark D.
Background: The extent of surgery required in the management of pediatric non-medial subperiosteal orbital abscess (SPOA) due to medically refractory complicated acute sinusitis is unknown. Objectives: The primary objective is to compare operative outcomes of children treated with combined endoscopic sinus surgery (ESS) and external orbital drainage (EOD) versus those treated with EOD alone. Methods: Retrospective case series from a tertiary children's hospital analyzing outcomes in children requiring surgical management for acute sinusitis complicated by non-medial SPOA between November 2007 and September 2019. Results: Sixteen children with a mean age of 9.4 years (95% CI: 7.3–11.4) met inclusion. Eleven (68.8%) underwent combined EOD and ESS, while five (31.2%) underwent EOD alone. Groups were similar in age, symptom duration, white blood cell count, C-reactive protein level, intraocular pressure, Lund-Mackay score, and abscess volume. There was no significant difference in median length of stay between patients treated with a combined approach versus those treated by EOD alone. Cultures identified non-beta-hemolytic Streptococcus species in 56.3% of patients, with Streptococcus intermedius representing the most common organism in 37.5%. In one case, ESS identified a pathogen not acquired via concomitant EOD, which did influence management. No child required a subsequent surgical procedure and there were no operative complications. Conclusions: The addition of ESS in the management of pediatric non-medial SPOA was not associated with a statistically different duration of hospitalization. Cultures from concomitant ESS rarely aided in diagnosis or antibiotic therapy. Further study should delineate the indications for ESS in these cases.